OS CONSELHOS MUNICIPAIS DE EDUCAÇÃO DA REGIÃO METROPOLITANA DA GRANDE VITÓRIA: UMA PROPOSTA DE FORMAÇÃO - Oliveira, Charla Barbosa de (2019)
This study analyzes the formation of participants of the municipal council of education of the Grande Vitória Metropolitan Region / ES (RMGV) in order to implement the strategies foreseen in the Municipal Education Plans (2015-2025). It seeks to identify